Inovasi Pembelajaran Guru Pendidikan Agama Islam Berbasis Teknologi Informasi - Tanwir Tanwir; Hamdanah Said (LPPM IAIN Parepare, 2018)
The study was aimed to: 1) describing the Islamic Education teachers’ performance on SMA in Parepare City; 2). describing the Senior Hight School Students’ learning outcomes in Parepare City; 3). Determining whether or not there was an influence of Islamic Education teachers’ performance on the Senioe Hight Schools students’ learning outcomes in Parepare City. The result of the study revealed that: 1) the Islamic Education teachers’ performance of Senior Hight Schools in Parepare City was in good category; 2) the students’ learning outcomes of Islamic Education tended to be in good category, 3) there was a significant influence of Islamic Education teachers’ performance on the Senior High Schools students’ learning outcomes in Parepare City. The study had implication: 1) the Islamic Education teachers realized the importance of a teacher working professionally, having high performance both in learning plan, learning implementation and evaluating the students’ learning outcomes, which can lead to the hight achievement of learning outcomes as well, 2) there was a concrete evidence of the implementation of education and learning practices in Senior High Schools which was necessary to be constantly improved.